Do patients with schizophrenia use prosody to encode contrastive discourse status? - Michelas, Amandine; Faget, Catherine; Portes, Cristel; Lienhart, Anne-Sophie; Boyer, Laurent; Lançon, Christophe; Champagne-Lavau, Maud (Frontiers in Psychology, 2014)
Patients with schizophrenia (SZ) often display social cognition disorders, including Theory of Mind (ToM) impairments and communication disruptions. Thought language disorders appear to be primarily a disruption of pragmatics, SZ can also experience difficulties at other linguistic levels including the prosodic one. Here, using an interactive paradigm, we showed that SZ individuals did not use prosodic phrasing to encode the contrastive status of discourse referents in French. We used a semi-spontaneous task to elicit noun-adjective pairs in which the noun in the second noun-adjective fragment was identical to the noun in the first fragment (e.g., BONBONS marron ‘brown candies’ vs. BONBONS violets ‘purple candies’) or could contrast with it (e.g., BOUGIES violettes ‘purple candles’ vs. BONBONS violets ‘purple candies’). We found that healthy controls parsed the target noun in the second noun-adjective fragment separately from the color adjective, to warn their interlocutor that this noun constituted a contrastive entity (e.g., BOUGIES violettes followed by [BONBONS] [violets]) compared to when it referred to the same object as in the first fragment (e.g., BONBONS marron followed by [BONBONS violets]). On the contrary, SZ individuals did not use prosodic phrasing to encode contrastive status of target nouns. In addition, SZ’s difficulties to use prosody of contrast were correlated to their score in a classical ToM task (i.e., the hinting task). Taken together, our data provide evidence that SZ patients exhibit difficulties to prosodically encode discourse statuses and sketch a potential relationship between ToM and the use of linguistic prosody.